The soybean lipoxygenase-fluorescein reaction may be used to assess antioxidant capacity of phytochemicals and serum. Issue 22 (19th May 2016) - Soccio, M.; Laus, M. N.; Alfarano, M.; Pastore, D.
Abstract : The new LOX-FL method highlights improvement of serum antioxidant capacity after antioxidant intake better than widely used methods. Abstract : Evaluation of the putative beneficial effects of food antioxidants by in vitro assays of the antioxidant capacity (AC) of food extracts sometimes appears questionable. A more realistic evaluation of antioxidant effectiveness may derive from the integration of in vitro assays with ex vivo assays of blood/serum/plasma AC after food intake. The aim of this study was to develop the novel lipoxygenase-fluorescein (LOX-FL) method to assay the AC of both food extracts and serum/plasma. This method was applied on both extracts from the antioxidant-rich dietary cereal supplement, Lisosan G, and serum (seven subjects) for 240 min after the intake of 20 g of supplement. The widely used ORAC and TEAC methods were used for comparison. The new LOX-FL method is based on the reaction between the soybean LOX-1 isoenzyme and FL in the presence of linoleic acid, which undergoes hydroperoxidation, thus generating physiological reactive species, including LOO˙, LO˙, HO˙ and 1 O2, which are able to quench FL. The quenching rate is slowed by antioxidants; this inhibition may be calibrated in terms of Trolox equivalents to assess the AC. Interestingly, the LOX-FL method discriminated the in vitro AC of four different Lisosan G extracts similarly to the ORAC and TEAC methods. In contrast, only the LOX-FL method was able to highlight a general increase in the serum AC (up to 40% after 30 min) after Lisosan G intake, thus confirming its physiological effectiveness by ex vivo serum assay. This quality of the LOX-FL method probably comes from the ability to highlight simultaneously different antioxidant mechanisms and to effectively show synergy among food phenols and endogenous serum antioxidants.